Pengaruh Strategi Pembelajaran Flipped Classroom Menggunakan e-Learning Kelase Terhadap Hasil Belajar Matematika Siswa - Nurul Fildzah Zatalini; Ilham Minggi; Rusli (Issues in Mathematics Education (IMED), 2017)
This research is a quasi experiment which aims to find out (1) the students' prior knowledge teach by using flipped classroom learning strategy and not using the flipped classroom learning strategy, (2) the students’ achievement teach by using the flipped classroom learning strategy and not using the flipped classroom learning strategy, (3) the influence of flipped classroom learning strategy to students’ achievement with regarding to students’ prior knowledge. The population of this research is 9th grade junior high school students in Gowa Regency. The sample of this research is 28 students as the experiment group and 30 students as control group. The data obtained are then analyzed descriptively and inferentially. After analyzed, the results of this study were (1) the average value of prior knowledge of the treatment group is in the low category whereas the average score of the students’ prior knowledge in the control group is in very low category, (2) the students' learning achievement of the treatment group is in the moderate category and the students' learning achievement in the control group is in a low category, (3) flipped classroom learning strategy influence students’ achievement with regarding to students’ prior knowledge